Phương pháp tổng hợp bộ điều chỉnh robust PID thông qua phân rã D - Lân, Lê Hùng (Journal of Computer Science and Cybernetics, 2016)
Based on D partition and new results in robust analysis thi presents a method of tuning robust PID controller by constructing stability domain with given margin for uncertain plant.